Perceptions of clinical care and research among African-American patients with lymphoma. Issue 8 (3rd July 2021) - Dance, Kaylin V.; Imbody, Conner B.; Chen, Lillian; McNeill, Lorna; Payne, Jackelyn B.; Flowers, Christopher R.
Abstract: Across lymphoma subtypes, African Americans experience disparities in clinical trial enrollment and outcomes. Understanding the needs of this population can aid addressing these disparities. Semi-structured interviews were conducted with 14 self-identified Black/African-American lymphoma patients to determine their perceptions and attitudes about aspects of treatment and research. Constant-comparative methods identified themes including trust in medical staff, lack of diagnosis information, interest in research, research priorities, and potentially unaddressed emotional needs. Patients trusted their doctors and desired more diagnosis information. Participants often did not consider the emotions surrounding their diagnoses and concentrated on positive attitudes during treatment. Most participants were interested in clinical trials to help future lymphoma patients. Participants suggested a range of future research topics emphasizing lymphoma etiology. Building on trusting doctor-patient relationships, expanding clinical trials information, addressing emotional needs, and aligning research objectives with patient concerns are potential strategies for increasing clinical trial enrollment among Black lymphoma patients.